Traffic channeling under uncertain conversion rates on e‐commerce platforms. (12th September 2022) - Yu, Peiwen; Zhang, Zhoupeng Jack; Li, Qing
Abstract: Traffic is the lifeblood of every e‐commerce platform. The question of how to channel traffic to merchants operating on a platform lies at the heart of platform management. We consider a platform on which two independent merchants sell their products. Merchants compete on inventory in the sense that some of the unmet demand at one merchant will spill over to the other. The platform channels traffic based on products' conversion rates to maximize the total sale on the platform. We show that traffic channeling plays three roles. First, it allows more efficient allocation of traffic; that is, the merchant with a high conversion rate is given a higher priority in receiving traffic. Second, it allows the platform to control demand spillover between the merchants to maximize total sales. The platform either facilitates or prevents demand spillover, depending on product substitutability. Third, traffic channeling intensifies competition between the merchants and hence increases the total inventory. More efficient allocation of traffic and the increase in inventory increase sales inequality between the merchants. In contrast, demand spillover decreases sales inequality. While the platform always benefits from traffic channeling, the merchants do not benefit when their products are moderately substitutable. Interestingly, when the two products are owned and sold by the same merchant, the opposite happens–traffic channeling always benefits the merchant but may hurt the platform. Our study provides a basis for informed discussions on how platforms should channel traffic in response to conversion rates, and how traffic channeling affects the welfare of merchants and platforms.